2001
DOI: 10.1242/jcs.114.8.1545
|View full text |Cite
|
Sign up to set email alerts
|

Superactivation of integrin αvβ3 by low antagonist concentrations

Abstract: Integrins are implicated in cell adhesion, migration and homeostasis. An important feature is their ability to adopt different affinity states that can be regulated by a variety of intra- and extracellular factors. To study affinity modulation of the integrin ectodomain by extracellular factors, we produced a soluble recombinant form of mouse integrin (α)v(β)3 in a mammalian expression system and isolated it to purity. We show that the two transmembrane truncated integrin subunits stably associate to form a fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(16 citation statements)
references
References 38 publications
(43 reference statements)
0
16
0
Order By: Relevance
“…54,57,58 The binding of RGD-based antagonists to αVβ3 produces similar changes in metal-ion coordination to those observed with the RGD-based antagonists to αIIbβ3 59 and also exposes a ligand-induced binding site (LIBS) on the β3 PSI domain for mAb AP5. 60−62 This partial agonist activity may contribute to inducing receptor extension, 63 priming the receptor to bind ligand at low doses in vitro, 64 enhancing angiogenesis ex vivo at sub-IC 50 concentrations, 62 and activating osteoclast signaling like that produced by natural ligands. 65 Many of the animal studies supporting a role for αVβ3 in the pathophysiology of disease have included evidence that cilengitide improves outcome.…”
Section: ■ Introductionmentioning
confidence: 99%
“…54,57,58 The binding of RGD-based antagonists to αVβ3 produces similar changes in metal-ion coordination to those observed with the RGD-based antagonists to αIIbβ3 59 and also exposes a ligand-induced binding site (LIBS) on the β3 PSI domain for mAb AP5. 60−62 This partial agonist activity may contribute to inducing receptor extension, 63 priming the receptor to bind ligand at low doses in vitro, 64 enhancing angiogenesis ex vivo at sub-IC 50 concentrations, 62 and activating osteoclast signaling like that produced by natural ligands. 65 Many of the animal studies supporting a role for αVβ3 in the pathophysiology of disease have included evidence that cilengitide improves outcome.…”
Section: ■ Introductionmentioning
confidence: 99%
“…To better analyze the effect of the cations, we only immobilized 0.25 μg/mL of α v β 3 . Even though the effects were marginal, the use of 0.5 mM of Mn 2+ instead of, or in addition to, 0.5 mM Mg 2+ (also tested by Legler et al 28 ) led to slightly lower binding (10 nM of 1a: OD ∼ 0.35 iso. 0.38), while the use of Mg 2+ alone at 1.0 mM even slightly increased the binding of 1a (10 nM of 1a: OD ∼ 0.41 iso.…”
Section: ■ Results and Discussionmentioning
confidence: 94%
“…Based on a report by Legler et al in 2001 that the affinity of α v β 3 to ligands, such as fibronectin or vitronectin, can be modulated using bivalent cations, 28 we then repeated our binding studies with 1a and α v β 3 in the presence of 1.0 mM CaCl 2 and 0.5 mM MgCl 2 in all buffers. In the presence of these cations, we found that binding of peptide 1a to α v β 3 was drastically improved and could be detected (OD ∼ 1.0) at 0.5 μg/mL of α v β 3 and 0.1 nM of 1a, respectively, which is equivalent to a ∼10000-fold reduction (Figure 2A).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The inhibition of network formation at a lower concentration can be reliably ascribed to the ability of GRGDG-NH 2 to bind and block the αvβ3 integrin by acting as an integrin antagonist blocking or decreasing cell migration and thus network formation . Indeed, RGD-like peptides are able to block the integrin binding site by competing with the RGD-containing ligands (vibronectin, fibronectin) . Network destruction by RGD-AuNPs and GRGDG-NH 2 could be due to the ability of small RGD-like peptides to act as potent integrin antagonist compounds that can disrupt the αvβ3 integrin–ligand interactions …”
Section: Discussionmentioning
confidence: 99%
“…75 Indeed, RGD-like peptides are able to block the integrin binding site by competing with the RGDcontaining ligands (vibronectin, fibronectin). 76 Network destruction by RGD-AuNPs and GRGDG-NH 2 could be due to the ability of small RGD-like peptides to act as potent integrin antagonist compounds that can disrupt the αvβ3 integrin−ligand interactions. 77 Overall, the results obtained in the in vitro experiments can be explained by considering (i) the overexpression of αvβ3 integrin in the B16F10 cell line, (ii) the affinity of RGD-like peptides for αvβ3 integrin, and (iii) the critical role of this integrin isoform in cell migration and tumor growth.…”
Section: Molecular Pharmaceuticsmentioning
confidence: 94%